Fábio Lucena: um senador Amazônida (1940-1987) - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
This dissertation approaches the biography of the banker, journalist and politician Fábio Pereira de Lucena Bittencourt (1940-1987), and proposes a reflection regarding his political practice in the historical context, and in the political field in which he acted. Our purpose was to seek in its journalistic and political activity during the period studied, an understanding of the Brazilian conjuncture during the military dictatorship and its slow process of redemocratization. Our main objective is to analyze the political trajectory of Fábio Lucena. Lucena's political practice coincides with the transition from military dictatorship in Brazil (1964-1985) to a democratic regime. In this sense, the analysis of its trajectory can contribute to the understanding of this emblematic moment of the History of Brazil.
Keywords: Fábio Lucena - Trajetória Política; Fábio Lucena - Biografia; Ditadura Militar; CIÊNCIAS HUMANAS: HISTÓRIA